Role of Phytoconstituents in Targeting Cytokines for Managing Pathophysiology of Lung Diseases - Maurya A.; Singh A.K.; Yadav H.; Mishra G.; Awasthi R.; Mishra S.K.; Chaudhary S.K. (My University, 2025)
Normal lungs can be distressed by internal as well as external factors which can be reason for producing diseases. The lungs respond against these factors via a protective mechanism known as inflammation. Cytokines, small secreted proteins, play a crucial role to control these inflammations, but overproductions of cytokines create many respiratory diseases (responsible for high mortality rates). These types of respiratory diseases are treated with the help of antiinflammatory agents to minimize the pulmonary inflammation. Medicinal plants and drugs derived from plants have numerous therapeutic effects when utilized by patients. Occurrence of several active phytoconstituents in plants is useful to treat many types of inflammatory diseases. The use of medicinal plants and phytoconstituents (alkaloids, flavonoids, terpenes, and others) as curative tool in pulmonary inflammation is increasing significantly. In the current book chapter, the role of medicinal plants and phytoconstituents for the managing pathophysiology of lung diseases is appraised. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2021.